A tetRA -based promoter system for the generation of conditional knockouts in Campylobacter jejuni - Cohen,EJ; Quek,RT; Beeby,M (2019)
Abstract Campylobacter jejuni is responsible for tens of millions of cases of gastroenteritis each year. Despite its prevalence and impact on human health, the repertoire of genetic tools available for researchers to study C. jejuni remains limited. In order to expand upon the genetic toolkit in this species, we have engineered a system for generating conditional knockouts based on the tetRA tetracycline-resistance cassette. This system exhibits tight repressibility and titratability of target-gene expression and will be useful for future research on this important human pathogen.